2018
DOI: 10.1002/em.22245
|View full text |Cite
|
Sign up to set email alerts
|

Bioflavonoids promote stable translocations between MLLAF9 breakpoint cluster regions independent of normal chromosomal context: Model system to screen environmental risks

Abstract: Infant acute leukemias are aggressive and characterized by rapid onset after birth. The majority harbor translocations involving the MLL gene with AF9 as one of its most common fusion partners. MLL and AF9 loci contain breakpoint cluster regions (bcrs) with sequences hypothesized to be targets of topoisomerase II inhibitors that promote translocation formation. Overlap of MLL bcr sequences associated with both infant acute leukemia and therapy‐related leukemia following exposure to the topoisomerase II inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…DNA reporter assays suggest that quercetin interferes with DNA repair mechanisms such as HR and C-NHEJ by inhibition of PI3K/Akt signaling. In support of these studies, exposure to multiple bioflavonoids promotes the generation of chromosomal translocations in a dose-dependent manner [29,87].…”
Section: Bioflavonoid Classification As a Covalent Or Traditional Topmentioning
confidence: 72%
See 2 more Smart Citations
“…DNA reporter assays suggest that quercetin interferes with DNA repair mechanisms such as HR and C-NHEJ by inhibition of PI3K/Akt signaling. In support of these studies, exposure to multiple bioflavonoids promotes the generation of chromosomal translocations in a dose-dependent manner [29,87].…”
Section: Bioflavonoid Classification As a Covalent Or Traditional Topmentioning
confidence: 72%
“…For example, among the flavonols, structure predicts that myricetin has high activity, quercetin has intermediate activity, and kaempferol has weak activity, if at all, as a covalent Top2 poison (Figure 4). Cell free studies support this and show that myricetin as well as epigallocatechin-gallate (ECGC) act as strong coalvent poisons, quercetin acts as a weak traditional poison, but kaempferol does not have this activity [29,87].…”
Section: Bioflavonoids As Covalent Top2 Poisonsmentioning
confidence: 98%
See 1 more Smart Citation
“…t(9;11) positive AML can occur primarily as a de novo neoplasm or as a result of previous therapy, for example t-AML, typically caused by topoisomerase II inhibitors (1517). It has been suggested that the topoisomerase II cleavage site and the DNase I hypersensitive site can colocalize in the break cluster regions of MLLT3 and KMT2A (16,18,19). Furthermore, an in vivo experiment reported the cleavage site of VP-16 (a topoisomerase II-like inhibitor) localized in the break cluster regions of KMT2A in a patient with AML (20).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, bioflavonoids can induce DNA cleavage at the same location in MLL and a partner gene as classic TOP2 poisons, and they can inhibit in vitro TOP2 activity to a similar extent as etoposide and doxorubicin [12]. Recent work demonstrated that quercetin and genistein can promote the formation of MLL / AF9 translocations in hematopoietic stem cells [143]. Overall, there is strong support for the role of TOP2 inhibition, from occupational exposure and/or maternal diet, in promoting DNA cleavage of oncogenic loci, as well as the subsequent translocations that drive adult and pediatric AML.…”
Section: The Role Of Top2-induced Breaks In Diseasementioning
confidence: 99%